2012
DOI: 10.1097/coh.0b013e328356682a
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability of HIV integrase inhibitors

Abstract: INSTIs are an important recent addition to the antiretroviral armamentarium, with good short-term and medium-term safety. Long-term data from ongoing clinical studies are needed for a definitive assessment of their safety profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…145 This could relate to the fact that they have only recently been brought into the pharmacopoeia. Evidence exists for a side effect of dyslipidemia, which could be considered a risk factor for increased cardiovascular disease, but are generally acceptable for clinical use.…”
Section: Other Antiretroviral Side Effects: Aging and Pismentioning
confidence: 99%
See 1 more Smart Citation
“…145 This could relate to the fact that they have only recently been brought into the pharmacopoeia. Evidence exists for a side effect of dyslipidemia, which could be considered a risk factor for increased cardiovascular disease, but are generally acceptable for clinical use.…”
Section: Other Antiretroviral Side Effects: Aging and Pismentioning
confidence: 99%
“…Evidence exists for a side effect of dyslipidemia, which could be considered a risk factor for increased cardiovascular disease, but are generally acceptable for clinical use. 145,146 …”
Section: Other Antiretroviral Side Effects: Aging and Pismentioning
confidence: 99%
“…In addition, treatment-experienced HIV-infected patients had comparable results when switched from raltegravir to an elvitegravir-containing regimen [46,52,[56][57][58]. A completed phase IIIb non-inferiority trial enrolling adults already suppressed on efavirenz or nevirapine or rilpivirine plus tenofovir/emtricitabine who were randomized to either remain in their current regimen or switch to elvitegravir/cobicistat/emtricitibine/tenofovir suggested that at 48 weeks (endpoint HIV RNA \50 copies/mL) the switch appeared efficacious and welltolerated with no emergent resistance.…”
Section: Elvitegravir Use In Adultsmentioning
confidence: 76%
“…The most common AEs seen with the use of INSTIs are gastrointestinal disturbances, such as diarrhea and nausea, but headache is also a common AE [61]. In addition, INSTIs have shown infrequent lipid elevations and low rates of metabolic abnormalities [61,62]. Nevertheless, raltegravir has been associated with creatinine phosphokinase (CPK) elevations and cobicistat, in the elvitegravir single-tablet formulation, is associated with benign increases in serum creatinine [61].…”
Section: Safetymentioning
confidence: 99%